Women Rectors and Leadership Narratives: The Same Male Norm? - Teresa Carvalho; Sara Diogo (MDPI AG, 2018)
This paper examines how two Portuguese women rectors constructed narratives on their path to leadership positions and their performance of leadership roles. The study is based on a qualitative empirical analysis based on life story interviews with two women rectors in Portugal. The results from this research suggest that women rectors tend to develop narratives about their professional route to the top as based on merit and hard work, and tend to classify their leadership experience as gender-neutral and grounded on the establishment of good relationships with their peers along their professional path. These narratives may contribute to reinforcing the male norm that leads other women to blame themselves for not being able to progress in their career, hindering the creation of an organisational environment that is open to the development of institutional policies to improve equal opportunities. Portugal is a very interesting case study, considering that despite the long history of its higher education system and the high participation of women in higher education, there were only two women rectors in the country until 2014.